2020
DOI: 10.1186/s12888-020-02745-3
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced individual placement and support (IPS) intervention based on the Model of Human Occupation (MOHO); a prospective cohort study

Abstract: Background: Employment is good for physical and mental health, however people with severe mental illness (SMI) are often excluded from employment. Standard Individual Placement and Support (IPS) is effective in supporting around 55% of people with SMI into employment or education. Current research considers enhancements to IPS to improve outcomes for those requiring more complex interventions. Clinicians need to better understand who will benefit from these enhanced IPS interventions. This study offers a new e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Additional interventions, such as motivational interviewing, can be used by the employment specialist to further enhance the client’s motivation [ 36 , 37 ]. This use of additional interventions is likely to reinforce the effects of IPS for clients [ 16 , 37 , 42 , 43 ]. The finding that the client’s relevant work experience, competences and/ or skills were experienced as facilitators to obtaining employment, also suggests that additional interventions or training for the client during the IPS trajectory may reinforce the effects of IPS [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional interventions, such as motivational interviewing, can be used by the employment specialist to further enhance the client’s motivation [ 36 , 37 ]. This use of additional interventions is likely to reinforce the effects of IPS for clients [ 16 , 37 , 42 , 43 ]. The finding that the client’s relevant work experience, competences and/ or skills were experienced as facilitators to obtaining employment, also suggests that additional interventions or training for the client during the IPS trajectory may reinforce the effects of IPS [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some barriers to obtaining employment identified in this study, such as the client’s lack of self-confidence and/ or self-esteem, appear to have psychosocial underpinnings. Although pre-employment assessments are not recommended in IPS programmes [ 13 ], this finding suggests that assessing psychosocial factors in an early phase of the IPS trajectory may be useful for identifying clients with psychosocial issues who would benefit from additional interventions [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative analysis by de Greef showed that the risk of disclosure of the medical diagnosis might represent a potential issue for people with mental conditions seeking employment (85). Lastly, since the spread of the IPS model, different variants and types were invented to fit the needs of specific population groups (50,86,87), explaining the individualistic approach to the implementation of this strategy and an opportunity for further development improvements and developments (88).…”
Section: Barriers and Facilitators Of Successful Ips Implementation And Employmentmentioning
confidence: 99%
“…The study found negligible effect modification by country, welfare system and labour market situations [ 11 ]. Yet, the challenge of sustainability in mainstream practice beyond trials is a well-known phenomenon [ 12 14 ] and we do not know as much about what happens in mainstream practice in the process of implementing IPS in a non-trial environment. Also, the implementation of IPS may be more country and culture specific than the efficacy of IPS.…”
Section: Introductionmentioning
confidence: 99%